Self-employed and parallel import project as options for resolving social and economic problems - O. M. Makhalina; V. N. Makhalin (Вестник университета)
The article briefly presents an overview of the recent situation in socio-economic sphere. The study analyzes causes and factors of citizens’ informal employment level growth, considers content of self-employment, existing realities, and emerging trends in labor market, and performs a comparative analysis of features of the choice between self-employment and individual entrepreneurship. The essence of parallel imports has been revealed, mechanism of its realization in the existing conditions of legal and economic restrictions considered, positive and negative consequences of its impact on the socio-economic development of Russia investigated. Main conclusions and provisions have been formulated, containing probable direction of the regulatory authorities’ activity, which should allow to realize to the fullest extent the potential of population employment growth embedded in self-employment of citizens through their involvement in the parallel import mechanism.